ANALYSIS OF PEAK EARTHQUAKE ACCELERATION (PGA) VALUE IN THE DUMAI DURI KANDIS ROAD AREA KM 68 + 975 USING PSEUDOSTATIC ANALYSIS - Tiara Mahardika; Muhammad Yusa; Syawal Satibi (LPPM Universitas Negeri Jakarta, 2023)
This study aims to analyze the acceleration value of peak earthquakes with pseudostatic in Riau Province using exploratory research. Earthquakes are one of the natural disasters that often occur in Indonesia. In addition to its high intensity, the impact caused often causes a lot of losses. As one of a high potentialy seismic activity province, Riau is vulnerable to earthquake disasters, the road sections are traversed by heavily loaded vehicles such as on Jalan Dumai Duri Kandis KM 68 + 975 which borders several areas at high risk of earthquakes, so an analysis of the acceleration value of peak earthquakes is needed. The results were found that the earthquake plan that can be used on the Dumai Duri Kandis KM 68 + 975 road section for analysis is PGA = 0.25-0.3g and PGA = 0.25g is taken, the average N-SPT value obtained is 10, based on the average N-SPT value obtained the site classification for its location in the form of soft soil, based on the site classification obtained, the amplification factor for the PGA Soft Land site class = 0.2, Ss = 0.5 is 1.7 while for the Soft Land site class PGA = 0.3, Ss = 0.75 is 1.2. After interpolating obtained FPGA value = 1.45 (for PGA = 0.25), the peak acceleration value of the earthquake on Dumai Kandis Road was 0.1088 g which was needed to analyze slope stability using soil parameter data sourced from laboratory to obtain more accurate safety factor.